ANALYZING THE TRANSLATION OF ENGLISH METAPHORS INTO INDONESIAN IN A NOVEL ENTITLED BRIDGET JONES'S DIARY BY HELEN FIELDING - Putri Mahardiani, - (2008)
This research paper is entitled Analyzing the Translation of English Metaphors into Indonesian in a Novel Entitled Bridget Jones's Diary by Helen Fielding. In conducting the study, the writer has two main questions to answer: (1) what kinds of metaphors are found and translated in the novel; and (2) what kinds of translation procedures are used by translator in translating metaphors. The data are collected from the novel in the form of textual evidence of the kinds of metaphors and the translation procedures. To analyze the collected data, the writer uses a descriptive method with a qualitative approach. This method allows the writer to elaborate the collected data. There are some steps in analyzing data: (1) reading thoughtfully both original novel and the translated version; (2) classifying the collected English metaphors into two types of metaphors as proposed by Larson (1984); (3) analyzing the translation procedures as proposed by Newmark (1988). Then, some calculations are employed in the forms of frequency and percentage to find tendencies in the use of metaphors and translation procedures. The findings show that there are two kinds of metaphors found and translated in the novel: dead metaphors (71 items or 66%) and live metaphors (36 items or 34%). Thus, the total number of the metaphors identified in the novel is 107 items. The translator of the novel, Amelia Listiani uses six procedures of translation in translating the kinds of metaphors presented. 'Synonymy' is the most frequently procedure used in translating metaphors that are found in the novel. There are 36 items (34%) of metaphors rendered by using this procedure. Meanwhile, the other translation procedures are 'literal' 24 items (22%), 'couplet' 21 items (20%), 'transposition' 13 items (12%), 'addition' 12 items (11%), and the smallest one 'reduction' 1 item (1%). It can be concluded that the use of metaphors is intended to give more emotional effect and to transfer the author's sense impressions. Moreover, the use of metaphors offers the readers with implied expressions that the readers need to figure them out in order to understand the work. The procedures of synonymy and addition might enable readers to familiarize metaphors through a clear and natural target language.